Influence of the Duration of Tectonic Evolution on Organic Matter Pore Structure and Gas Enrichment in Marine Shale: A Case Study of the Lower Silurian Longmaxi Shale in Southern China - Li, Xin; Wang, Pengfei; Wang, Shuai; Jin, Can; Zhang, Chen; Zhao, Rui; Jiang, Zhenxue (Frontiers in Earth Science, 2022)
The exploration and development of the shale in the Lower Silurian Longmaxi Formation in the Chongqing area has shown that gas production here is commercially viable. In contrast, the Longmaxi Formation shale in Hunan shows that gas production is not commercial. Why is there such a difference between the Chongqing and Hunan areas for the same formation. A mount of previous studies showed that gas is stored primarily in the organic matter (OM) pores in shale. This study has investigated the Longmaxi shale from two well locations in Chongqing and Hunan in order to understand whether differences in pore structure are the cause of the difference in commerciality in the two areas. The formation burial histories were established, analyzing samples for mineral composition, total organic carbon (TOC) content, thermal maturity (Ro), and OM pore structures. The results show that the Longmaxi shale in Chongqing and Hunan has similar TOC content and Ro. The average TOC content is above 3.0% for samples from both areas, and the thermal maturity was all between 2.4 and 2.9%. OM pores of the Longmaxi shale in Chongqing are abundant in number and relatively large sized, with mostly circular and oval shapes. In contrast, the number and size of the OM pores in the Longmaxi shale in Hunan are small, and the shape is irregular. OM pore structure of the Longmaxi shale in Chongqing is therefore favorable for preservation of gas. The poor pore structure of the Longmaxi shale in Hunan is not conducive to gas preservation. The OM pore structure difference of the Longmaxi shale in Chongqing and Hunan is determined by the formation burial history. The Longmaxi shale in the Chongqing area experienced rapid burial in the Early Jurassic and rapid uplift in the Late Cretaceous. The Longmaxi Formation in Hunan experienced rapid burial in the Early Triassic and rapid uplift in the Early Jurassic. The long evolution time (100 Ma) of the Longmaxi shale in Chongqing produced a large amount of gas supply and enough storage space (OM pores) for the gas occurrence, which makes the amount of gas be preserved in geological history. The short evolution time (50 Ma) of the Longmaxi shale in Hunan produced insufficient gas supply and not enough OM pores in reservoir, which leads to gas loss in geological history, resulting in low gas content. Therefore, to evaluate the potential of shale gas, the evolution time of organic matter must be considered. In other words, the time interval between rapid subsidence and uplift of formation during geological history must be considered.